Life cycle analysis of monocrop and multicrop in conventional and organic vegetable production systems in Tayabas, Quezon, Philippines. (February 2019) - Abasolo, A; Zamora, O
Abstract: Attaining food security is directly linked to increasing agricultural production to meet the needs of the exponentially increasing population. Extensive efforts in the past to improve crop production resulted to massive land conversion, deforestation and inappropriate use of modern technologies among others. Comparative assessment of the potential impacts of conventional and organic vegetable production systems is valuable because agriculture is one of the major contributors to environmental degradation. This study assessed and compared the environmental burdens of conventional and organic vegetable production systems in both monocrop and multi-cropping using the environmental Life Cycle Analysis (LCA) approach. The data gathered from in-depth interviews with farmers and farm surveys in Tayabas, Quezon, were used to determine the cropping system that has significant potential contributions to Global Warming Potential (GWP), Acidification Potential (AP), Eutrophication Potential (EP) and Human Toxicity Potential (HTP) with land area and kg −1 of vegetable as functional units. The conventional vegetable multi-cropping system contributed 4.10E-02 kg CO2 -eq kg −1 to GWP higher than the monocrop with only 3.69E-02 kg CO2 -eq kg- 1 potential contribution. Organic multicrop contributed less to GWP with only 2.48E-02 kg CO2 -eq kg −1 . AP of conventional multicrop is also higher with 6.79E-03 g SO2 -eq kg −1 as compared to the combined AP of organic monocrop and multicrop. Further, conventional vegetable production contributed higher HTP with 6.22E+06 g 1, 4 DCB -eq kg −1 than organic. This study shows that organic production system has lower environmental burdens and a better alternative to improve food crop production while protecting the environment.